Сучасний стан міжнародно-правового співробітництва у зміцненні демократії - Свида, Т. О.; Svida, T. (My University, 2012)
The article is devoted research of process of formation in international law a principle of democracy according to which the states should correspond the fixed international law to democratic standards. Studying of modern international legal acts testifies that the international law accurately enough focuses the states on a democratic way of development of their political systems.
Свида Т. О. Сучасний стан міжнародно-правового співробітництва у зміцненні демократії / Т. О. Свида // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 170-179.
Keywords: демократія; демократизація; міжнародне право; міжнародні стандарти; демократия; демократизация; международное право; международные стандарты; democracy; democratization; international law; the international standards